Análisis del sistema penitenciario mexicano y los retos de la reinserción social - Avila Navarro, Andrea Gabriela (Archivos de criminología, seguridad privada y criminalística, 2022)
The objective of this research topic focuses on analyzing the problems that the Mexican prison system is going through, to end with a final reflection of those detailed in this article, in addition, it will analyze what the prison treatment consists of and will address the subject of criminal recidivism and its possible causes. The type of research that was carried out for this article is of a mixed type, so that I use the qualitative AND quantitative method, because an analysis was carried out and I explain the behavior of people who participate in illegal activities and who continuously They enter the social reintegration centers, obtaining as a result issued by the INEGI that in 2019, 112,811 people entered a penitentiary center while 102,799 people discharged, triggering more income than discharges